Factors Affecting Public Interest in Bank Sumut Syariah Products - Dwi April Yani Simangungsong; Raissa Muthia Syahrani Hasibuan; Ridha Shafina Nur; Muhammad Lathief Ilhamy Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
As a financial bridging body, in carrying out its operations banks are grouped into two, namely conventional banks and Islamic banks, Islamic banks certainly need the function and role in Indonesia, therefore Islamic banks must improve the quality of their performance to realize a Syariah banking system that is able to perform efficiency with a healthy system. Increasing the number of customers and public awareness about the existence of Islamic banks as one of the important things in order to realize the country of Indonesia to be a pioneer of Islamic financial development in the world. The method used by the author is the method of literature review. With the method of literature review, the author conducts a review of the scientific literature on a topic of problems and conducts a critical analysis of some things that affect the interest of customers to make purchases of products marketed by Bank Sumut Syariah and awareness of them and interest in the products offered. Based on the results of literature riview conducted can be concluded that the interest of consumers to buy products offered by Bank Sumut Syariah influenced by several things, namely : (1) quality of Service and profit sharing (2) products offered and promotions carried out (3) trying to raise awareness of the brand and interest in Syariah products.